COVID-19 during Gestation: Maternal Implications of Evoked Oxidative Stress and Iron Metabolism Impairment - Jorge Moreno-Fernandez; Julio J. Ochoa; Catalina De Paco Matallana; Africa Caño; Estefania Martín-Alvarez; Javier Sanchez-Romero; Juan M. Toledano; Maria Puche-Juarez; Sonia Prados; Susana Ruiz-Duran; Lucia Diaz-Meca; María Paz Carrillo; et al. (Antioxidants, 2022)
COVID-19 has reached pandemic proportions worldwide, with considerable consequences for both health and the economy. In pregnant women, COVID-19 can alter the metabolic environment, iron metabolism, and oxygen supply of trophoblastic cells, and therefore have a negative influence on essential mechanisms of fetal development. The purpose of this study was to investigate, for the first time, the effects of COVID-19 infection during pregnancy with regard to the oxidative/antioxidant status in mothers’ serum and placenta, together with placental iron metabolism. Results showed no differences in superoxide dismutase activity and placental antioxidant capacity. However, antioxidant capacity decreased in the serum of infected mothers. Catalase activity decreased in the COVID-19 group, while an increase in 8-hydroxy-2’-deoxyguanosine, hydroperoxides, 15-FT-isoprostanes, and carbonyl groups were recorded in this group. Placental vitamin D, E, and Coenzyme-Q10 also showed to be increased in the COVID-19 group. As for iron-related proteins, an up-regulation of placental DMT1, ferroportin-1, and ferritin expression was recorded in infected women. Due to the potential role of iron metabolism and oxidative stress in placental function and complications, further research is needed to explain the pathogenic mechanism of COVID-19 that may affect pregnancy, so as to assess the short-term and long-term outcomes in mothers’ and infants’ health.